2011
DOI: 10.1074/jbc.m111.273482
|View full text |Cite
|
Sign up to set email alerts
|

Three Lysine Residues in the Common β Chain of the Interleukin-5 Receptor Are Required for Janus Kinase (JAK)-dependent Receptor Ubiquitination, Endocytosis, and Signaling

Abstract: Background: A complete understanding of the role of ␤c ubiquitination in IL-5R biology is currently lacking. Results: We identified three ␤c lysine residues that are required for JAK kinase binding to the receptor. Conclusion: JAK kinase binding to ␤c via 3 lysines is essential for receptor ubiquitination. Significance: We provide new mechanistic details regarding IL-5R biology, which is important for understanding eosinophil physiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 62 publications
(63 reference statements)
1
14
0
Order By: Relevance
“…Alternatively, increased JAK2 and LYN expression could be correlated with a negative feedback loop that down-regulates GM-CSFR ␤c levels in TF-1 cells. The ubiquitination of ␤c in response to IL-5 stimulation is dependent on JAK2 activity (68,69). In CBL-Y371H-and CBL-C384R-expressing cells, the enhanced JAK2 activity can potentially lead to increased ubiquitination of the ␤c by other ubiquitin ligases, resulting in decreased overall expression of the receptor subunit.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, increased JAK2 and LYN expression could be correlated with a negative feedback loop that down-regulates GM-CSFR ␤c levels in TF-1 cells. The ubiquitination of ␤c in response to IL-5 stimulation is dependent on JAK2 activity (68,69). In CBL-Y371H-and CBL-C384R-expressing cells, the enhanced JAK2 activity can potentially lead to increased ubiquitination of the ␤c by other ubiquitin ligases, resulting in decreased overall expression of the receptor subunit.…”
Section: Discussionmentioning
confidence: 99%
“…Sorting of receptors into MVB provides intracellular signaling platforms and/or subsequent recycling of the receptor to the plasma membrane and/or leads to their lysosomal degradation (26). The importance of compartmentalized signaling has already been described for a number of other receptor systems, where ubiquitination and subsequent endocytosis of the receptors are needed for proper signal transduction (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified a cluster of three membrane-proximal GMRβc lysine residues (K457, K461 and K467) required for receptor-mediated ubiquitylation [10]. SOCS-1 mediated GMRβc ubiquitylation, which is stabilized and visualized in the presence of MG132, was markedly attenuated in GMRβc(3K>R) substitution mutant ( Fig.…”
Section: Resultsmentioning
confidence: 81%
“…Plasmids encoding Flag-SOCS-1, -2 and -3, SOCS-1▵SOCSBox have been previously described [11]. The triple lysine K>R mutant of βc, (K457R, K461R, K467R) [10] was generated using the QuikChange Site-Directed Mutagenesis Kit from Invitrogen (Burlington, ON, Canada) and the following primer pair: 5′-CTGCGCAGAAGGTGGGAGGAGAGGATCCCCAACCCCAGCAGGAGC …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation